Kesediaan Pegawai Untuk Berbagi Pengetahuan Melalui Sistem Manajemen Pengetahuan - Oky Fardiyono; Anita Maharani; Etty Puji Lestari (Fakultas Ekonomi Universitas Islam 45, 2020)
The Directorate General of Taxes is one of the most vital government institutions, where around 85 percent of the financing of the Republic of Indonesia comes from tax revenue. The Riau Islands Directorate General of Taxes Regional Office, as a new office established since October 2018, certainly needs office instruments and employees who can adapt and learn quickly like other regional offices in order to achieve the tax revenue target. For this reason, increasing the capacity of tax officials must always be increased, one of which is through knowledge sharing. The purpose of this study was to determine whether personal benefit factors, normative considerations, rewards, organizational support, social interaction, levels of empathy, and levels of courage affect the willingness of tax employees to share knowledge. This research was conducted on employees in the Regional Office of the Riau Islands Directorate General of Taxes with a population of 658 people. The sample used was 234 tax employees. The research method used is a quantitative method, namely multiple linear regression. After testing the validity and reliability, the collected data is tested for each variable component of the willingness to share knowledge. The test results show that personal benefits, normative considerations, appreciation, organizational support, social interaction, level of empathy and level of courage affect the willingness of tax employees to share knowledge within the Riau Islands Directorate General of Regional Taxes.